Influence of Zinc on Histoplasma capsulatum Planktonic and Biofilm Cells - Pires, Ana Carolina Moreira da Silva [UNESP]; Carvalho, Angélica Romão [UNESP]; Vaso, Carolina Orlando [UNESP]; Mendes-Giannini, Maria José Soares [UNESP]; Singulani, Junya de Lacorte [UNESP]; Fusco-Almeida, Ana Marisa [UNESP] (MDPI, 2024)
Histoplasma capsulatum causes a fungal respiratory disease. Some studies suggest that the fungus requires zinc to consolidate the infection. This study aimed to investigate the influence of zinc and the metal chelator TPEN on the growth of Histoplasma in planktonic and biofilm forms. The results showed that zinc increased the metabolic activity, cell density, and cell viability of planktonic growth. Similarly, there was an increase in biofilm metabolic activity but no increase in biomass or extracellular matrix production. N′-N,N,N,N–tetrakis–2-pyridylmethylethane–1,2 diamine (TPEN) dramatically reduced the same parameters in the planktonic form and resulted in a decrease in metabolic activity, biomass, and extracellular matrix production for the biofilm form. Therefore, the unprecedented observations in this study highlight the importance of zinc ions for the growth, development, and proliferation of H. capsulatum cells and provide new insights into the role of metal ions for biofilm formation in the dimorphic fungus Histoplasma, which could be a potential therapeutic strategy.
Keywords: biofilm; Histoplasma capsulatum; histoplasmosis; metallic ions; TPEN; zinc